Traits and Stories: Links Between Dispositional and Narrative Features of Personality - McAdams, D.P; Anyidoho, N.A; Brown, C; Huang, Y.T; Kaplan, B; Machado, M.A (Journal of Personality (Blackwell Publishing), 2004)
Dispositional traits and life narratives represent two different levels of personality that have not previously been empirically linked. The current study tested five hypotheses connecting Big-Five traits to life-narrative indices of emotional tone, theme, and structure. Students (Study 1) and adults (Study 2) completed a self-report measure of the Big- Five traits and provided extended written accounts of either ten (students) or eight (adults) key life-narrative scenes, including life high points, low points, and turning points. Content analysis of the narrative data revealed that for both samples Neuroticism was positively associated with an emotionally negative life-narrative tone, Agreeableness was correlated with narrative themes of communion (e.g., friendship, caring for others), and Openness was strongly associated with the structural complexity of life narrative accounts. Contrary to prediction, however, Conscientiousness was not consistently associated with themes of agency (e.g., achievement, self-mastery) and Extraversion was unrelated to positive narrative tone. The results are discussed in the context of contemporary research and theorizing on the narrative study of lives and the relation of narrative research in personality to more conventional, trait-based approaches. In an effort to organize the many different ways that personality psychologists do and might explore the multifaceted nature of human individuality, McAdams (1994, 1995, 2001a; Hooker & McAdams, in press) proposed a three-level model for personality constructs. At Level 1 reside dispositional traits—global, internal, and comparative dispositions that account for consistencies perceived or expected in behavior from one situation to the next and over time (e.g., Goldberg, 1990; McCrae & Costa, 1987). At Level 2, characteristic adaptations are contextualized facets of human individuality that speak to motivational, social-cognitive, and developmental concerns in personality. Included at this level are constructs such as current concerns and strivings, goals and motives, defensive and strategic operations, conditional patterns, and other constructs that are contextualized in time, place, or social role (e.g., Little, 1999; Mischel & Shoda, 1995). At Level 3, finally, are integrative life stories—internalized and evolving narratives of the self that speak to how a person understands him- or herself and his or her position in the world in broadly existential terms (Habermas & Bluck, 2000; McAdams, 1993, 2001b; Singer, 1995). If dispositional traits sketch an outline and characteristic adaptations fill in some of the details of human individuality, then internalized life stories speak to what a person’s life may mean in the overall. How are personality constructs from these three different levels related to each other? McAdams (1995) argued that there is no reason to expect strong symmetry and consistency across different levels of personality description, for people’s lives are typically complex and often contradictory. Furthermore, conceptual mappings for one level (e.g., the five-factor model for Level 1) may not do justice to the indigenous features of other levels. Relations across levels, therefore, remain an open empirical question. A few recent studies have examined the question as it pertains to relations between Levels 1 and 2. For example, Roberts and Robins (2000) linked Big-Five factors and the narcissism trait to goal profiles, and Roccas, Sagiv, Schwartz, and Knafo (2002) documented associations between the five factors and value clusters. There is also an established literature showing that motives and goals (Level 2) are positively associated with some life-narrative themes (Level 3). For example, studies have shown that individual differences in goals and motives for power are positively correlated with life-narrative themes of agency (e.g., self-mastery, influencing others, attaining victory and status), whereas motives and goals for intimacy are positively associated with life-narrative themes of interpersonal communion (e.g., love and friendship, caring for others, dialogue) (McAdams, 1982, 1984, 1985; McAdams et al., 1981; McAdams, Hoffman, Mansfield, & Day, 1996; Woike, 1995; Woike, Gersekovich, Piorkowski, & Polo, 1999; Woike & Polo, 2001). McAdams and colleagues, furthermore, have shown that high scores on generativity (a developmental concern of midlife – Level 2 – indicating a strong commitment to promoting the well-being of youth and the next generation) are consistently linked with a life-narrative format that emphasizes themes of personal destiny, redemption, and forward progress in life (McAdams & Bowman, 2001; McAdams, Diamond, de St. Aubin, & Mansfield, 1997). Virtually nothing, however, is known about how dispositional traits (Level 1) might relate to narrative features of personality (Level 3). One reason for the absence of data in this regard may be the very different methodologies and epistemological assumptions employed by social scientists who specialize in these two respective domains of inquiry. Trait psychologists value rigorously quantitative and psychometric investigations that aim to test hypotheses with large samples, while many narrative psychologists prefer qualitative, idiographic studies that aim to discover new psycho-literary forms (e.g., Gregg, 1995; Rosenwald & Ochberg, 1992). Closer to the mainstream of psychological science, trait research follows what Bruner (1986) describes as the paradigmatic mode of thought and inquiry, seeking to validate clear and empirically replicable assertions about behavior. By contrast, life-story scholars often place a high premium on the subjective interpretation (hermeneutics) of the life text, as they operate in Bruner’s narrative mode of inquiry, where stories are used, both by the investigator and the subject, to express the lived experience of a particular human being (Cohler, Hostetler, & Boxer, 1998). The current investigation seeks to bridge the gap between these two approaches by exploring relations between Level 1 traits and Level 3 life narratives in samples of college students and adults. Like trait studies, the current investigation employs sample sizes that are large enough and scoring procedures that are objective enough to test hypotheses about how traits relate to other phenomena. Like narrative studies, the investigators have collected a substantial amount of rich and highly personal life-story data from each subject, providing a small narrative case study for each participant in the study. The written narratives are coded for content themes and then related to scores on a self-report measure of the Big-Five traits ( John & Srivastava, 1999). The investigation tests five simple hypotheses— one for each of the Big-Five traits—drawn from a reading of the trait and life-narrative literatures. The first two hypotheses link the traits of Extraversion (E) and Neuroticism (N) to what McAdams (1993) termed narrative tone. Every story has a characteristic emotional tone, ranging most simply from extreme positivity (happiness, joy, optimism—think comedy) to extreme negativity (despair, fear, pessimism—think tragedy). In a parallel fashion, a number of researchers have provided data to support the argument that positive affectivity and negative affectivity form the emotional cores of E and N, respectively (e.g., Watson & Clark, 1984, 1997). For the current study, then, the first hypothesis is that E should be positively associated with a positive affective tone in life-narrative accounts; the second hypothesis is that N should be associated with a negative life-narrative tone. Hypotheses 3 and 4 link the traits of Conscientiousness (C) and Agreeableness (A) to what McAdams (1985) termed a narrative’s thematic lines. Whereas tone refers to the overall emotional feel of a story, theme gets to the issue of plot and movement—how characters act to accomplish their intentions. According to Bruner (1986) a story is fundamentally about the ‘‘vicissitudes of intention’’ organized in time (p. 17). Characters’ intentional acts spread out over time to make the story’s plot. Thematic lines refer to what kinds of intentions characters display—that is, what they are trying to get, achieve, or avoid. In life stories, two general thematic lines are what Bakan (1966) called agency and communion (McAdams, 1985). Agency encompasses characters’ intentional movements toward self-mastery, self-control, achievement, and power. Communion encompasses love, intimacy, care, and the sense of being part of a community. In a parallel fashion, C and A may be viewed as orthogonal constructs comprising an interpersonal circumplex for Level 1 traits, with C predicting behavior suggestive of self-control and achievement (Barrick & Mount, 1991; Hogan, Hogan, & Roberts, 1996) and A linked, at least in theory, to warm and caring behavior (Graziano & Eisenberg, 1997). Therefore, the third hypothesis is that C should be positively associated with narrative themes of agency; the fourth is that A should be associated with narrative themes of communion. Hypothesis 5 is about Openness to Experience (O) and the concept of narrative complexity (McAdams, 1985). Simple stories contain few characters, straightforward plots, and clear resolutions; complex stories may have a multitude of characters and interwoven plots, and they may suggest multiple meanings and ambiguous resolutions. Among the different aspects of O, researchers have identified dimensions of cognitive and emotional complexity (McCrae & Costa, 1997). Persons high in O are described as original, imaginative, and complex. McCrae and Costa (1980) found that O was positively associated, furthermore, with higher stages of ego development, which also indicate higher levels of cognitive complexity (Loevinger, 1976). McAdams (1985) showed that adults with high levels of ego development expressed a greater number of generic plots in their life stories compared to those scoring low in ego development. Therefore, this study’s fifth hypothesis is that O should be positively associated with the structural complexity of life-story accounts. The five hypotheses are tested in two parallel studies. In the first study, 125 college students provide detailed narrative accounts of ten significant moments or scenes in their life stories, such as lifenarrative high points, low points, turning points, important childhood scenes, and scenes of moral decision making. The accounts are scored for indices of emotional tone, thematic lines, and narrative complexity, and these scores are correlated with self-report Big Five traits. The second study follows a similar procedure with a sample of 51 adults, who provide comparably detailed accounts of eight significant life-narrative scenes.
Keywords: Traits and Stories; Links; Dispositional; Narrative; Personality